A2ML1 Inhibits Esophageal Squamous Cell Carcinoma Progression and Serves as a Novel Prognostic Biomarker - Xiaoyun Zhang; Chaogui Tang; Jianchun Lian; Yuzhang Jiang (Canadian Journal of Gastroenterology and Hepatology)
Studies have established a correlation between α2-macroglobulin-like 1 (A2ML1) and the prognosis of lung, pancreatic, and breast cancers; however, research on its involvement in the pathogenesis of esophageal carcinoma remains limited. Therefore, in this study, we aimed to investigate the role of A2ML1 in the progression of esophageal squamous cell carcinoma (ESCC). Immunohistochemical staining was employed to assess the expression level of A2ML1 protein in both tumor and adjacent normal tissues of patients with ESCC. The Kaplan–Meier method, along with univariate and multivariate Cox risk ratio analyses, was used to determine survival rates and prognostic factors. Furthermore, two human ESCC cell lines, KYSE30 and KYSE150, were used to assess the effect of A2ML1 overexpression on cell proliferation and apoptosis. A human apoptosis antibody kit was also used to analyze the downstream action proteins of A2ML1, and a nude mouse xenotransplantation model was used to evaluate the effect of A2ML1 on ESCC tumorigenesis in vivo. The protein level of A2ML1 in ESCC tissues was significantly lower than that in normal esophageal tissues, and higher A2ML1 protein levels were associated with smaller ESCC tumor sizes and improved tumor-specific survival rates. Multivariate analysis established A2ML1 as a novel independent prognostic factor for ESCC. Moreover, A2ML1 overexpression significantly inhibited ESCC cell proliferation and promoted apoptosis. A2ML1 consistently inhibited tumor growth in mouse models. Furthermore, the human apoptotic antibody kit results showed increased expression of the proliferation-inhibiting protein p21 downstream of KYSE150 cells overexpressing A2ML1. Our findings demonstrate that a correlation exists between A2ML1 and ESCC prognosis and that A2ML1 plays an antitumor role in ESCC progression. This study underscores the potential of A2ML1 as a novel biomarker for predicting the prognosis of ESCC.